Model Pelayanan Promosi Kesehatan Jiwa Berbasis Maasyarakat: Literatur Riviwe - Lina Eta Safitri; Nurbaiti Zulkaidah; Surti Hatiya; Sulis Susilawati; Eldo Tawa Gara Meha; Alexander Umbu Neka Pajaga (Jurnal Medika Nusantara, 2024)
Mental health is a health problem that cannot be separated from other health problems, and is one of the problems that will become a burden for the state and families due to premature death and disability. Health services are services provided to students related to health, both preventive (prevention of disease), promotive (improving health), curative (treatment of disease) and reabilitative (recovery). Health Promotion is an effort to improve community capabilities through learning from, by, for and with the community, so that they can help themselves, as well as developing activities that are community resourced, appropriate to local social culture and supported by health-oriented public policies. This study uses all articles presented in the form of a literature review regarding "Community-based mental health promotion service models". Articles taken from Indonesian language journals that are relevant to the topic and published in the time span starting from 2015-2023. Based on the results of the literature review of the five journals analyzed, all of them provide significant differences in the questionnaire scores which can be seen from the average scores before (pretest) and after (posttest) the intervention. Mental health is a health problem that cannot be separated from other health problems, and is one of the problems that will become a burden for the state and families due to premature death and disability. Health services are services provided to students related to health, both preventive (prevention of disease), promotive (improving health), curative (treatment of disease) and reabilitative (recovery). Based on the results of the literature review of the five journals analyzed, all of them provide significant differences in the questionnaire scores which can be seen from the average scores before (pretest) and after (posttest) the intervention. Mental health cadres are people who volunteer to provide mental health services for ODGJ through promotive, preventive and rehabilitation services under the supervision of professional health workers, in a community-based mental health promotion health service model.